The Anxiety in English Foreign Language Speaking Class The Case of Seventh Semester Students at Universitas Muhammadiyah Bengkulu - Erza Kurnia Zahari; Ivan Achmad Nurcholis (Indonesian Journal Of Education, 2025)
This study seeks to assess the amount of speaking anxiety among seventh-semester students at Universitas Muhammadiyah Bengkulu, as well as to discover the factors that influence this anxiety and its impact on their English speaking ability. Speaking anxiety in a foreign language is a regular occurrence among students, which can impede the learning process and language acquisition. In the context of English language learning, this anxiety is frequently generated by a variety of circumstances, including fear of being judged by others, a lack of speaking experience, and academic pressure. This research uses a quantitative approach using a survey design. This study's population comprises of seventh-semester students from the English Language Education Program at Universitas Muhammadiyah Bengkulu, with a random sample. The questionnaire employed in this study was developed to assess the amount of speaking anxiety and its underlying causes. The acquired data was analyzed using descriptive statistics to offer an overview of anxiety levels and inferential statistics to determine the links between the contributing variables.The results indicate that a significant majority of students experience high levels of speaking anxiety when speaking in English, with a percentage reaching 70%. Contributing factors to this anxiety include fear of negative evaluation from peers and instructors, lack of preparation before speaking, and previous negative experiences in English speaking situations. Furthermore, this study also finds that speaking anxiety negatively impacts students' self-confidence and their ability to communicate effectively in English. The conclusion of this research emphasizes the importance of understanding speaking anxiety in the context of English language learning. There is a need for better teaching strategies and psychological support to help students overcome this anxiety, enabling them to enhance their confidence and speaking abilities in English. This study is expected to contribute to the development of more effective and responsive English language teaching methods that address students' needs.